Obscene Pornographic Materials Analysis of the Criminal Responsibility of Purchasers of Private Customized "Al Face-swapping" - Xia, Xiaoxi (Transactions on Social Science, Education and Humanities Research, 2024)
The advancement of technology has given rise to the emergence of Al, which is like a double-edged sword, bringing convenience and efficiency while also posing risks and challenges. While enjoying its intelligent services, we must be vigilant against potential threats and use this powerful tool wisely,allowing technology to serve human well-being rather than become a shackle that binds us.This paper strongly opposes the emergence of private customized "Al face-swapping" obscene pornographic materials, which not only seriously infringe upon the legitimate rights and interests of portrait rights holders, but also disseminate obscene content and corrupt social norms. The individuals who purchase such services are participating in illegal activities, violating not only the portrait rights of others but also relevant laws and regulations by disseminating obscene materials. Therefore,according to legal provisions, they should bear corresponding criminal responsibilities. Such behaviors are supposed to be banned, safeguard social order and good customs, and ensure that the legitimate rights and interests of individuals are fully protected. The spread of such materials poses a serious threat to society, and action must be taken to prevent its further occurrence.